Pengaruh Manajemen Pelayanan Pengunjung dalam Meningkatkan Kepuasan Pengunjung di Lembang Park & Zoo - Putri Rahayu; Yudha Munajat Saputra; Gilang Pratama Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Tourist attraction managers can improve visitor satisfaction by optimizing their human resources. This means that this study was conducted to determine how visiting tourists assess service management. The main factor in consumer satisfaction is their perception of the quality of service received. The expected results are to provide information about this service management process to help tourists assess staff performance during the operation of Lembang Park & Zoo. This study uses a quantitative approach design, using a descriptive method approach with a data collection technique, namely a survey. . By distributing questionnaires and google forms. Other populations are visitors who are active in the Lembang Park & Zoo area, which is 410,000. then the number of samples to be taken in this study is 100 tourists. The sampling technique in this study uses simple random sampling. Visitor service management has a strong correlation with visitor satisfaction at Lembang Park & Zoo, because the service provided by a destination is an effective thing that must ensure that the quality of service provided to visitors is consistent and satisfactory, including the speed in responding to complaints and the availability of friendly and trained staff to improve visitor satisfaction. Affirming that visitor service management is not only important in daily operations but is important in improving the image of a good destination and the attractiveness of a tourist destination. Visitor satisfaction has been shown to increase when their interactions with visitor service staff are positive and satisfying, meaning that this shows that in reliable service can bring benefits can greatly help tourist destinations by increasing visitor satisfaction and making tourists come back.